Valuación del capital intelectual, su contabilización y presentación como activo intangible en los estados financieros - Yangali Vicente, Judith Soledad (2018)
The objective of the research was to determine the methodologies applied in the valuation of intellectual capital, the accounting and presentation as an intangible asset in service companies. The type of research is basic orientation, also called fundamental or pure. The execution of the research project was carried out through the application of the analytical, comparative and explanatory method. The research design is non-experimental, cross-sectional. The population is made up of all those companies, whose main headquarters are in Metropolitan Lima, whose main activity is service provision, which was a total of 1,150,987 companies. The design of the sample is simple random sampling. The sample size is equal to 384 companies. The technique used was the survey, the instrument used was the questionnaire. Research has made it possible to verify the strategic value of intellectual capital in companies and the role of intangible resources as a means to obtain a competitive advantage and therefore achieve superior business results. It has been verified that there is consensus regarding the components of intellectual capital: human capital, structural capital and relational capital. It concludes by stating that the valuation of intellectual capital generates value for companies, through recognition, accounting and presentation as an intangible asset in the financial statements.